CITIZENAPP: YET ANOTHER SOCIAL MEDIA PLATFORM FOR PUBLIC FACILITY MONITORING IN SIDOARJO - Jagad Yudha Awali; Irwan Alnarus Kautsar; Arif Senja Fitrani (Jurnal Teknoinfo, 2022)
Public facilities are one of the important assets that support citizens' daily activities. Its benefits can be shared by a large number of people in a given region. However, many public facilities found in the Sidoarjo Regency area are not maintained, such as roads, bus stops, trash cans, sidewalks, parks, street lighting, traffic lights, and traffic signs, which can cause discomfort when using public facilities. These conditions could be minimized when local governments involve societies to maintain or monitor them. The objective of this study is to create an integrated smart city mobile application that can be used to report damage to public facilities using the QR Code that has been attached to them. In this study, the waterfall method was used as a development method. The result of this study is a mobile application which is expected to be useful for monitoring public facilities in Sidoarjo. According to the results, the application looks helpful and compatible with all Android devices.